Revisiting the Woman of Samaria and the Ambiguity of Faith in John 4:4-42. - TOAN DO (Catholic Biblical Quarterly, 2019)
In Das Evangelium des Johannes (1941), Rudolf Bultmann argues that John’s account of the Samaritan woman in John 4:4-42 serves only as a catalyst in bringing the Samaritans to Jesus. Her strange question μήτι οὗτός ἐστιν ὁ χριστός (v. 29, NRSV: “He cannot be the Messiah, can he?”) arouses the townspeople’s curiosity and they come to Jesus (v. 30). John’s profound sense of irony and ambiguity suggests that the woman may not have come to belief in Jesus, but the townspeople have (πιστεύομεν, “we believe,” v. 42). Bultmann’s reading is no longer accepted replaced now by the widely welcomed view that the woman has come to faith in Jesus—a conversion story. Revisiting John 4:4-42 here, I offer a semantic argument and suggest that scholarship on John 4 ought to consider the ambiguity of the account the woman may not have arrived at faith in Jesus.